A Review of fuel additives' effects and predictions on internal combustion engine performance and emissions - Sarbani, Daud; Mohd Adnin, Hamidi; R., Mamat (AIMS Press, 2021)
In recent years, there has been an increasing interest in additives for fuel research in the field of internal-combustion engine. Many studies have been conducted to improve the performance and emissions of the engine. Many kinds of additives in the form of solid, liquid, and gas have been used. The objective of this review is to examine the effects of having additives on the performance and emission of internal combustion engine. Additives such as alcohol, hydrogen, and metal oxides are proven to be successful to improve performance or reduce emission. Results from selected papers are discussed and summarised in a table. With the new development in nanotechnology, many researchers have shown an increased interest in carbon-based. In recent years, there has been an increasing interest in additives for fuel research in the field of internal-combustion engines. Many studies have been conducted to improve the performance and emissions of the engine. Many kinds of additives in the form of solids, liquids, and gases have been used. The objective of this review is to examine the effects of having additives on the performance and emissions of an internal combustion engine. Additives such as alcohol, hydrogen, and metal oxides are proven to be successful in improving performance or reducing emissions. Results from selected papers are discussed and summarised in a table. With the new developments in nanotechnology, many researchers have shown an increased interest in carbon-based nanoparticles such as multi-walled carbon nanotubes (MWCNT) and single-walled carbon nanotubes (SWCNT). Lately, with the discovery of graphene production techniques, graphene nanoplatelets (GNP) have also been applied as fuel additives. In addition to understanding the effects of the additives on the engine performance and emissions, researchers extended the research to predict the outcome of the performance and emissions. nanoparticles such as multi-walled carbon nanotube (MWCNT) and single-walled carbon nanotube (SWCNT). Lately, with the discovery of graphene production techniques, graphene nanoplatelets (GNP) also has also been applied as fuel additives. In addition to the understanding the effects of the additives to the engine performance and emissions, researchers extended the research to predict the outcome of the performance and emissions. The experiments involving the predictions efforts are summarised in a table. From the summary, it is found that the prediction of the GNP as fuel additive effects to the performance and emissions has not yet been explored. This gap is an opportunity for researchers to explore further.